2002
DOI: 10.1634/stemcells.20-1-73
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Apoptosis and Increase in Polyploidization of Megakaryocytes by Stem Cell Factor During Ex Vivo Expansion of Human Cord Blood CD34 + Cells Using Thrombopoietin

Abstract: Thrombopoietin (TPO) is widely used for ex vivo expansion of hematopoietic stem cells. Previously, we have reported that TPO induces a characteristic pattern of apoptosis, and the TPO-induced apoptosis is closely associated with megakaryocyte (MK) differentiation. In the present study, several cytokines, flt3-ligand, stem cell factor (SCF), interleukin-3 (IL-3), IL-6, IL-11, leukemia inhibitory factor, G-CSF, and erythropoietin, which are known to affect megakaryocytopoiesis, have been evaluated to elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Other researchers have shown that human megakaryocytopoiesis is under the regulation of a network of different cytokines including GM-CSF, IL-6 and SCF [37][38][39][40][41][42][43][44]. These hematopoietic growth factors can either act alone or in synergy with TPO to stimulate the proliferation and maturation of MK progenitor cells [45][46][47][48][49][50]. Consequently, our results support that human MSCs from the three sources could promote megakaryocytic differentiation and platelet formation from CD34 þ HPCs by mechanisms of cytokine secretion and physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have shown that human megakaryocytopoiesis is under the regulation of a network of different cytokines including GM-CSF, IL-6 and SCF [37][38][39][40][41][42][43][44]. These hematopoietic growth factors can either act alone or in synergy with TPO to stimulate the proliferation and maturation of MK progenitor cells [45][46][47][48][49][50]. Consequently, our results support that human MSCs from the three sources could promote megakaryocytic differentiation and platelet formation from CD34 þ HPCs by mechanisms of cytokine secretion and physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, much of the research work has focused on identifying the best cytokines and their optimal combinations to promote Mk proliferation, differentiation or both. Thus, interleukin (IL)-1, IL-3, IL-6, IL-9, IL-11, stem cell factor (SCF), and platelet-derived growth factor (PDGF), to name a few, were all shown to synergize or complement thrombopoietin (TPO) and promote ex vivo megakaryopoiesis [1][2][3][4][5][6][7]. Along this line, our group has recently reported a new cytokine cocktail (BS1) composed of TPO, SCF, IL-6, and IL-9 that was developed using a statistical design approach to maximize specifically the maturation of Mks derived from cord blood (CB) cells.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of thrombopoietin (TPO) has allowed the generation of megakaryocytes (MK) and platelets in ex vivo cultures. TPO and various cytokines have been shown to act in synergism for optimal MK viability and yield (Kie et al, 2002;Sigurjonsson et al, 2002;Su et al, 2001;Williams et al, 1998). We recently reported that early and late variations of cytokine concentrations could promote the in vitro TPO-dependent generation of MKs from CD34enriched cells cord blood (CB) (Proulx et al, 2003).…”
Section: Introductionmentioning
confidence: 99%